kreatif, Open Ended ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA SMP MUHAMMADIYAH 3 SURABAYA DENGAN PENDEKATAN OPEN-ENDED: KEMAMPUAN BERPIKIR KREATIF DENGAN PENDEKATAN OPEN ENDED - nadia, rochmatun_; Daesusi, Ruspeni (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2023)
Abstract: This study aims to analyze the creative thinking skills of SMP Muhammadiyah 3 Surabaya students in learning mathematics using an open-ended approach. This research is a qualitative descriptive study with research subjects of class VII students at SMP Muhammadiyah 3 Surabaya. The instrument used in this study was a description of questions consisting of 4 questions. The research results obtained from the students' answers in solving the questions showed that as many as 20 out of 30 students had quite high creative thinking skills. The percentage of creative thinking skills is 67%.Keyword: Mathematics Learning, Creative Thinking Ability, Open-Ended Approach